Efficacy of abatacept tapering therapy for sustained remission in patients with rheumatoid arthritis: Prospective single‐center study. (30th August 2018) - Yoshida, Shuzo; Kotani, Takuya; Kimura, Yuko; Matsumura, Yoko; Yoshikawa, Ayaka; Tokai, Nao; Ozaki, Takuro; Nagai, Koji; Takeuchi, Toru; Makino, Shigeki; Arawaka, Shigeki
Abstract: Aim: To investigate whether remission can be sustained for rheumatoid arthritis (RA) patients after tapering abatacept (ABT). Method: All patients were naïve to biological disease‐modifying anti‐rheumatic drugs (bDMARDs) and in low or moderate Disease Activity Score of 28 joints with C‐reactive protein (DAS)28‐CRP). ABT was administrated intravenously (IV) or subcutaneously (SC) for 36 weeks to patients with RA, who had not previously received bDMARDs. As the ABT tapering protocol, ABT was administrated SC at 125 mg every 2 weeks for 12 weeks in patients with remission. RA disease activity was assessed by DAS28‐CRP and ultrasonography. Remission was assessed by defining it as DAS28‐CRP <2.3. Results: Of the 51 patients, 84.3% were women (mean age 68.7 ± 10.2 years, mean disease duration 7.7 ± 10.2 years). Twenty‐nine patients achieved remission and a power Doppler (PD) score ≤1 at each joint at 36 weeks, followed by tapering ABT. Of these patients, 25 sustained DAS28‐CRP remission, and DAS28‐CRP was not significantly elevated (1.62 ± 0.41 to 1.69 ± 0.49) at 48 weeks, but the total PD score was significantly elevated (1.52 ± 1.21 to 2.59 ± 2.81 P  =   0.049). Longer disease duration, higher DAS28‐CRP at 24 weeks, and higher total PD score at 24 weeks were predictors of an elevated total PD score after tapering ABT therapy. Conclusion: These findings suggest that ABT tapering is a promising short‐term strategy to sustain remission in patients with RA, and ultrasonography is a useful tool for monitoring disease activity after tapering ABT.